2018
DOI: 10.1002/lio2.175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PI3K Pathway in HPV‐Associated Oropharyngeal Cancer With and Without Tobacco Exposure

Abstract: ObjectivesThe aim of the study was to evaluate whether HPV associated OPSCC with tobacco exposure follows a different carcinogenic pathway compared to HPV associated OPSCC without tobacco exposure and to investigate its prognostic significance. The question was addressed with focus on components of the PI3K pathway.Methods184 patients with newly diagnosed OPSCC treated with curative intent were consecutively enrolled. The expression level of p16, p53, PI3K, mTOR, and PTEN was assessed by immunohistochemistry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…1,2 HPV-associated tumors more frequently have phosphoinositide 3-kinase (PI3K) gene variations independent of tobacco exposure. 3,4 By exploiting this oncogenic addiction phenotype, aspirin and other nonsteroidal anti-inflammatory drugs (NSAIDs) have been identified as potential chemotherapeutic agents owing to the effect they have on cyclooxygenase inhibition, which is required for prostaglandin synthesis. 5 Concurrent use of NSAIDs has been shown to be associated with a survival advantage for colorectal cancer and a wide range of cancer histologies.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 HPV-associated tumors more frequently have phosphoinositide 3-kinase (PI3K) gene variations independent of tobacco exposure. 3,4 By exploiting this oncogenic addiction phenotype, aspirin and other nonsteroidal anti-inflammatory drugs (NSAIDs) have been identified as potential chemotherapeutic agents owing to the effect they have on cyclooxygenase inhibition, which is required for prostaglandin synthesis. 5 Concurrent use of NSAIDs has been shown to be associated with a survival advantage for colorectal cancer and a wide range of cancer histologies.…”
Section: Introductionmentioning
confidence: 99%
“…The continued development of targeted agents against this signaling pathway highlights the need to study the prognostic significance of MTOR pathway activation. For patients with HNSCC, there have been several studies examining this question that have resulted in inconsistent findings although the majority of investigations indicate that overexpression of MTOR is associated with poorer prognosis. As HPV+ and HPV− tumors have a different mutational spectrum, we have specifically asked the question whether MTOR expression differed between the subtypes and whether it was associated with prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to us, Kiessling et al [47] in 184 patients with oropharyngeal SCC did not report significant influence of mTOR expression on survival, however, contrary to us, they found significantly higher incidence of mTOR overexpression among p16 negative tumors. In turn, some authors, in the groups of patients with oropharyngeal cancers [48,49], have reported opposite results, i.e. inferior survival for patients with tumors overexpressing mTOR.…”
Section: Pik3ca Gene and Apobec3bmentioning
confidence: 99%
“…This protein is a surrogate marker of HPV presence and its use is related to risk of false positive results obtainment. On the other hand, taking into account the possibility of treatment with mTOR inhibitors, such as everolimus [48] or rapamycin [50] in HNSCC patients, the question about mutual relation between HPV infection and mTOR expression requires further studies.…”
Section: Pik3ca Gene and Apobec3bmentioning
confidence: 99%